High-Temperature (550–700°C) Chlorosilane Interactions with Iron. Issue 10 (18th August 2016) - Aller, Josh; Mason, Ryan; Walls, Kelly; Tatar, Greg; Jacobson, Nathan; Gannon, Paul
Abstract : Chlorosilane species are commonly used at high temperatures in the manufacture and refinement of ultra-high purity silicon and silicon materials. The chlorosilane species are often highly corrosive in these processes, necessitating the use of expensive, corrosion resistant alloys for the construction of reactors, pipes, and vessels required to handle and produce them. In this study, iron, the primary alloying component of low cost metals, was exposed to a silicon tetrachloride-hydrogen vapor stream at industrially-relevant times (0–100 hours), temperatures (550–700°C), and vapor stream compositions. Post exposure analyses including FE-SEM, EDS, XRD, and gravimetric analysis revealed formation and growth of stratified iron silicide surface layers, which vary as a function of time and temperature. The most common stratification after exposure was a thin FeSi layer on the surface followed by a thick stoichiometric Fe3 Si layer, a silicon activity gradient in an iron lattice, and finally, unreacted iron. Speculated mechanisms to explain these observations were supported by thermodynamic equilibrium simulations of experimental conditions. This study furthers the understanding of metals in chlorosilane environments, which is critically important for manufacturing the high purity silicon required for silicon-based electronic and photovoltaic devices.